PHOTOCATALYTIC DEGRADATION OF VIOLET-RR WITH SOLAR IRRADIATION USING TIO2 CATALYST - Fatma Yuka Desri (Lembaga Layanan Pendidikan Tinggi Wilayah X, 2021)
Violet-RR (C34H14Cl2O2) is one of the most common classes of Vat dyes used in the textile industry. These dyes are stable, toxic and can inhibit solar-light penetration into the waters system. In this study, Vat Violet-RR dye was degraded by using TiO2 as a catalyst under UV and solar-light irradiation. Some parameters i.e., irradiation time, catalyst mass and energy sources were studied. The reduction of dye concentration was measured by UV-Vis spectrophotometer at a wavelength 554 nm. The optimal catalyst mass obtained was 9 mg. Degradation percentage of Vat Violet-RR dyes obtained by photolysis without catalyst under UV and solar-light irradiation were 4.09% and 13.51%, respectively. The presence of TiO2 catalyst increased the degradation percentage to be 35.15% and 81.15% for 300 minutes irradiation. Based on the results, solar-light irradiation gives better results on Vat Violet-RR degradation than UV-light. Keywords: Degradation; Photolysis; Vat; Violet-RR; TiO2